Double taxation treaties as a catalyst for trade developments: A comparative study of Vietnam's relations with asean and eu member states - A. D. Pham; Pham Ha; Kim Cuong Ly (Journal of Risk and Financial Management, 2019)
Employing a panel gravity model and Generalized Least Squares (GLS) estimation technique, this study documents the effect of double taxation treaties on the bilateral trade of Vietnam with ASEAN member states, thereby making an extensive comparison with its EU partner countries. Our findings indicate the significant contributions of the tax treaties to Vietnam's trade performance, not exclusively with ASEAN but also with EU partner countries. Nevertheless, under some circumstances, the conclusion of tax treaties seems ineffective in strengthening export capacity or narrowing trade deficits for Vietnam. This is primarily due to the unidirectional movement of trade associated with tax treaty conditions, viz., imports from the advanced economies into Vietnam. Besides, the role of tax treaties as a dynamism of Vietnam's export growth remains opaque during recent years.
Keywords: 330; ASEAN; double taxation treaty; gravity model; trade